2017
DOI: 10.1007/s00520-017-3631-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of taxane-induced peripheral neuropathy receiving treatment and prescription patterns in patients with breast cancer

Abstract: One-fifth of breast cancer patients who were treated with taxane-based chemotherapy experienced TIPN receiving treatment, and its risk factors were paclitaxel use, old age, overweight, and metastatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 25 publications
10
49
3
1
Order By: Relevance
“…A prior study similarly reported physician-assessed CIPN toxicity grades that were lower than patientreported scores. 38 The findings of the current study corroborate other studies 2,3,8,39,40 reporting higher CIPN toxicity in patients treated with paclitaxel compared with docetaxel.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A prior study similarly reported physician-assessed CIPN toxicity grades that were lower than patientreported scores. 38 The findings of the current study corroborate other studies 2,3,8,39,40 reporting higher CIPN toxicity in patients treated with paclitaxel compared with docetaxel.…”
Section: Discussionsupporting
confidence: 89%
“…[41][42][43] In that literature, marital satisfaction, spousal support, and spousal responses to pain reportedly can contribute to psychological distress (depressive symptoms, anxiety symptoms, and mood disorders) which, in turn, is associated with pain dimensions, including symptom severity. 4,11,39,40,44 In the current study, a history of vigorous exercise prior to chemotherapy was not identified as a factor in the development of CIPN, although other studies have shown significantly reduced CIPN in women who were physically active prior to receiving chemotherapy. In our multivariable model, these quality-of-life measures were collected before, not after, neurotoxic chemotherapy was received.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Patients with higher BMI, lower Patient-KPS scores, and lengthy regimens reported a significantly greater number of severe toxicities. The finding pertaining to BMI may reflect the association between obesity and higher symptom severity for chemotherapy-induced peripheral neuropathy that has been observed in prior studies [35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 71%
“…Chemotherapy-induced peripheral neuropathy (CIPN) is a disabling side-effect, known to impair daily function and diminish quality of life [32]. Commonly used chemotherapeutic agents reported to cause neurotoxic effects include platinum derivatives, taxanes [40], vinca alkaloids, epothilones and newer agents (e.g thalidomide and bortezomib) [48]. The predominant sensory phenotype in patients treated with oxaliplatin or docetaxel is sensory loss affecting both upper and lower extremities.…”
Section: Introductionmentioning
confidence: 99%